Cover Image. (19th May 2022) - Lin, Liangjie; Zhang, Qinhe; Wang, Nan; Jiang, Ke; Lin, Yanqin; Chen, Zhong; Song, Qingwei; Liu, Ailian; Wang, Jiazheng
Abstract : The cover image is based on the Research Article Evaluation of brown adipose tissue with intermolecular double‐quantum coherence magnetic resonance spectroscopy at 3.0 T by Liangjie Lin et al., https://doi.org/10.1002/nbm.4676 .